2011
DOI: 10.1111/j.1445-2197.2011.05869.x
|View full text |Cite
|
Sign up to set email alerts
|

Solitary left axillary metastasis after curative surgery for right colon cancer

Abstract: [No abstract available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…A search of the National Library of Medicine’s PubMed database identifies six case reports, each describing one patient with axLN metastasis of primary colorectal cancer 1–6 (Table 1). …”
Section: Introductionmentioning
confidence: 99%
“…A search of the National Library of Medicine’s PubMed database identifies six case reports, each describing one patient with axLN metastasis of primary colorectal cancer 1–6 (Table 1). …”
Section: Introductionmentioning
confidence: 99%
“…Intercommunicating lymphatic flow and backflow of lymph from the paraaortic node to the thoracic duct may be the most direct route by which the cancer spread to the axilla. 3 Although hematogenous spread is less likely, it cannot be completely ruled out. Venous plexus drainage could be a route of possible dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…Only one other case report has noted solitary metastasis to the axilla following right hemicolectomy of the distal ascending colon. 3 In a related case, a patient had been diagnosed with breast cancer and gastric cancer prior to the metastasis of colon adenocarcinoma to axillary lymph nodes. 4 If metastasis has already occurred for previously diagnosed malignancies, the likelihood of colon adenocarcinoma metastasis is much higher.…”
Section: Introductionmentioning
confidence: 99%
“…In our literature review, we found four cases of late recurrence in axillary lymph nodes, always on the left side, in patients with primary colon carcinoma. In three of the cases, the primary tumor was of the descending colon and in the fourth case was of the cecum [1]- [4].…”
Section: Discussionmentioning
confidence: 99%
“…Other common metastatic sites are lung, peritoneum and ovary. Disease dissemination to lymph nodes other than the local ones is rare, with only four cases reported, as far as we know, of disease recurrence in axillary lymph nodes in patients with primary cancer of the colon [1]- [4].…”
Section: Introductionmentioning
confidence: 99%